(untitled) (Dissertare, 2021)
In this essay, the problems derived from the control of pests and diseases in crops are presented through the application of technologies that cause alterations to the planet’s biosphere, in most cases irreversible. This panorama suggests the urgent need to substitute such technologies for an integrated management of pests and diseases (MIPE for its acronym in Spanish), as a more environmentally responsible alternative, avoiding the dangerous secondary effects of the application of agrochemicals for the human and animal health. The work is qualitative, with a documentary design based on bibliographic review techniques and supported by content analysis as its interpretation technique. The principles established by different authors in the concepts of social responsibility (RS for its acronym in Spanish) suggest that a reflection that leads to a new vision in the face of such vulnerable nature is essential, not as a legal obligation of companies, but as a voluntary commitment to social awareness of the economic sector, in order to avoid the risks of environmental deterioration. The purpose of this document is to analyze the application of MIPE in vegetable crops, as an alternative for the fulfillment of Environmental Social Responsibility or social eco-responsibility, where ethics is included and sustainability is guaranteed. The existing tools in the MIPE are wide and varied. The producer, based on his experiences, can apply them without risk to his own health, that of his family, employees and consumers, with social and ethical responsibility.